2013
DOI: 10.1021/pr400127j
|View full text |Cite
|
Sign up to set email alerts
|

Improved Nα-Acetylated Peptide Enrichment Following Dimethyl Labeling and SCX

Abstract: Protein N-terminal acetylation is one of the most common modifications occurring co- and post-translationally on either eukaryote or prokaryote proteins. However, compared to other protein modifications, the physiological role of protein N-terminal acetylation is relatively unclear. To explore the biological functions of protein N-terminal acetylation, a robust and large-scale method for qualitative and quantitative analysis of this modification is required. Enrichment of N(α)-acetylated peptides or depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…The tryptic peptides were labeled as described previously 53 . Briefly, 4 μL of 37% formaldehyde was added to the lyophilized peptides in 100 μL of 0.1 M sodium acetate (pH 5–6).…”
Section: Methodsmentioning
confidence: 99%
“…The tryptic peptides were labeled as described previously 53 . Briefly, 4 μL of 37% formaldehyde was added to the lyophilized peptides in 100 μL of 0.1 M sodium acetate (pH 5–6).…”
Section: Methodsmentioning
confidence: 99%
“…In their study, 576 non-redundant N α -acetylated peptides were identified from 50 µg of cytosolic proteins extracted from HepG2 cells. Notably, the whole process was completed in 24 h and N α -acetylated peptides of some protein isoforms, such as β-actin/γ-actin, ERK1/ERK2, α-centractin/β-centractin and ADP/ATP translocase 2 and 3, were simultaneously detected from the SCX flow-through fraction [100].…”
Section: Applications Beyond Quantitative Analysismentioning
confidence: 99%
“…It is highly useful in solid‐phase synthesis of peptides (SPPS), peptidomimetics, and organic molecules . Acylation can be used to determine the degree of coupling and for capping in SPPS . Peptides derived from protein sequences are often acetylated at their N‐terminus to eliminate the extra positive charge and mimic the peptide bond .…”
Section: Introductionmentioning
confidence: 99%
“…Acylation can be used to determine the degree of coupling and for capping in SPPS . Peptides derived from protein sequences are often acetylated at their N‐terminus to eliminate the extra positive charge and mimic the peptide bond . The acetylation of lysine residues is a naturally occurring post‐translational modification that has many regulatory roles .…”
Section: Introductionmentioning
confidence: 99%